Understanding war an annotated bibliography - Potholm, Christian P. (War trilogy ;, 2016)
Understanding War divides war material into eighteen overarching themes of analysis and fifty seminal topics. In the process, it gives the reader access to the broadest possible array of material across both time and space, beginning with the earliest forms of warfare and concluding with the contemporary situation.